Activating Victim Constituency in International Criminal Justice - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 2009)
This article lays out why in the context of global crime, crime control and the legitimacy of global governance, a victim constituency makes sense in terms of the stated aims of international criminal justice and of a wider ‘new morality’ on which it should be grounded. The incapacity to confront appropriately the consequences to victims of global crime has tended to mean that international criminal justice and the governance that flows from it are unsatisfactorily entwined with sectarian international relations and narrow cultural inclusion. Therefore, in governance terms alone, the conceptualization of global crime victims should be expanded and emancipated from their current more procedurally restricted standing. As a consequence, the citizenship and standing necessary to enjoy international criminal justice would be more fairly realized. This article begins by making the case for why victims should be positioned in a place of priority as the constituency for international criminal justice. It then moves to demonstrate how, through ‘communities of justice,’ a sharper victim focus could make international criminal justice more accountable. This theme runs through the article and links the case for a transformed criminal trial process to a new age of global governance.